Development of best practice recommendations for the safe use of pulmonary hypertension pharmacotherapies using a modified Delphi method. (17th January 2019) - Smith, Zachary R; Rangarajan, Krishna; Barrow, Jennifer; Carter, Danielle; Coons, James C; Dzierba, Amy L; Falvey, Jennifer; Fester, Keith A; Guido, Maria R; Hao, Diana; Ou, Narith N; Pogue, Kristen T; et al.
Abstract: Purpose: The Delphi method was used to develop best practice recommendations (BPR) for safe use of pulmonary hypertension (PH) pharmacotherapies and to describe the pharmacist's role in provision of care. Methods: A core group reviewed PH medication-safety literature and developed initial BPR. Pharmacists practicing at PH-accredited Centers of Comprehensive Care who met defined PH expert criteria were invited to participate on an expert panel. In round 1 of a 4-round Delphi process, expert input was provided on the BPR. Feedback was incorporated into BPR for the next round. Round 2 proceeded in identical fashion to round 1. In round 3, BPR were deliberated in a teleconference and underwent voting at the cessation of the round using a 5-point Likert scale. Median scores of < 2.5, 2.5–3.75, and > 3.75 resulted in a best practice statement being rejected, reviewed in round 4, or accepted in the final BPR, respectively. In round 4, the remaining BPR were discussed and underwent voting. BPR were assigned a level of evidence and strength of recommendation based on voting results. Results: Eleven PH experts agreed to participate and met expert inclusion criteria, along with 2 pharmacists from the core group, bringing the total number of expert panel members to 13. To guide safe use of PH pharmacotherapies, 26 BPR were developed, categorized into 5 practice domains, comprising the PH Care Center accreditation process, inpatient practice, formulary management, diagnostics, and ambulatory care. BPR included provisions for safe use of parenteral prostacyclin agents and healthcare practitioner education. Conclusion: The Delphi method was used to develop BPR to guide safe use of PH pharmacotherapies.